Improving kinetic modelling of magnesium hydrogenation by including interfacial polarisation and interstitial hydrogen clustering behaviour within the site availability model - Marcus J. Adams; Alastair Stuart; Gavin S. Walker; David M. Grant (Journal of Magnesium and Alloys)
Recent work analysing magnesium hydrogenation using Reflecting Electron Energy Loss Spectroscopy (REELS) and Density Function Theory (DFT) has indicated interfacial polarisation and interstitial hydrogen clustering influence the reaction rate. The site availability model has been modified to include interstitial hydrogen clustering within the site availability factor and interface polarisation using interface treatment. The new model, SAM-CV-S, has demonstrated improved modelling of magnesium hydrogenation across wide operating conditions, such as temperatures from 330 to 400 °C and pressures up to 40 bar. This wide applicability makes it a robust model that can be used to simulate bed performance in solid-state hydrogen stores. Thus, the site availability factor successfully combines interstitial hydrogen clustering with thermal resistance effects, which are known to strongly influence metal hydride reactor designs at scale. The next phase of the model is to incorporate a predictive hydrogen capacity method into the model.